Editorial Special Issue on OMN 2022 - Wibool Piyawattanametha; Onur Ferhanoğlu; John X. J. Zhang (IEEE Photonics Technology Letters, 2023)
We are pleased to provide readers with the newest and important technologies presented at the International Conference on Optical MEMS and Nanophotonics 2022 (OMN 2022), through this Special Issue published by the IEEE Photonics Technology Letters (PTL) journal. The Optical Micro- and Nano Systems (OMN) conferences have surged in prominence over the recent years, mirroring the rapid advancements and burgeoning interest in the realm of optics and photonics technology for diverse applications from medical imaging, environmental sensing, to autonomous driving. OMN epitomizes the amalgamation of theory and practice, facilitated by our increasing technical prowess to engineer micro- and nano-scale structures and dynamic elements purpose-built for the interaction and manipulation of light.
Keywords: Photonic and Optical Devices